Development of Learning Cycle-Based Science Learning Devices to Improve Elementary School Students' Creative Thinking Ability - Siswadi Siswadi; Asri Fuadi; Abu Dharin (Postgraduate, University of Mataram, 2023)
The educational goals listed above have not been optimally achieved. Schools in Indonesia generally tend to train students in terms of receiving knowledge, memory, and reasoning or logical thinking so that little portion is given to train creative thinking skills. This research is development research that develops learning tools including lesson plans, worksheets, student textbooks, and assessment instruments. This research consists of two stages of implementation, namely the stage of developing learning tools and the stage of testing the devices that have been developed. Science learning tools based on the 5E Learning Cycle to train creative thinking skills that have been developed are declared valid and can be used in science learning activities in elementary schools.